Mechanisms of platelet-derived growth factor-BB in restoring HIV Tat-cocaine-mediated impairment of neuronal differentiation - Yang, Lu (Mol Neurobiol, 2015)
Diminished adult neurogenesis is known to play a key role in the pathogenesis of diverse neurodegenerative disorders such as HIV-associated neurological disorders (HAND). Cocaine, often abused by HIV-infected patients, has been suggested to worsen HIV-associated CNS disease. Mounting evidence also indicates that HIV-infection can lead not only to neuronal dysfunction or loss, but can also negatively impact neurogenesis, resulting in generation of fewer adult neural progenitor cells (NPCs) in the dentate gyrus of the hippocampus, brain area critical for memory and learning. The crucial role of Platelet-Derived Growth Factor-BB (PDGF-BB) in providing tropic support for the neurons as well as in promoting NPC proliferation has been demonstrated by us previously. However, whether PDGF-BB regulates neuronal differentiation especially in the context of HAND and drug abuse remains poorly understood. In this study we demonstrate that pre-treatment of rat hippocampal NPCs with PDGF-BB restored neuronal differentiation that had been impaired by HIV Tat & cocaine. To further study the intracellular mechanism(s) involved in this process, we examined the role of transient receptor potential canonical (TRPC) channels in mediating neuronal differentiation in the presence of PDGF-BB. TRPC channels are Ca(2+)-permeable, nonselective cationic channels that elicit a variety of physiological functions. Parallel but distinct ERK, Akt signaling pathways with downstream activation of CREB were found to be critical for neuronal differentiation. Pharmacological blocking of TRPC channels resulted in suppression of PDGF-mediated differentiation and PDGF-BB-induced activation of ERK and Akt, culminating also to inhibition of PDGF-induced activation of CREB. Taken together these findings underpin the role of TRPC channel as a novel target regulating cell differentiation mediated by PDGF-BB. This finding could have implications for development of therapeutic interventions aimed at restoration of Tat and cocaine-mediated impairment of neurogenesis in drug abusing HAND patients.